A Cross-Country Comparison of School-Based Social Capital Effects upon Reading Literacy Based on PISA Data - Hongqiang Liu; Jan Van Damme; Wim Van Den Noortgate (SAGE Open)
Addressing the gap in cross-cultural understanding of school-based social capital, this study examines its effects on student reading literacy across 14 economies using PISA 2009 data, selected for Parent Questionnaire availability. A two-stage analysis involved country-specific two-level hierarchical linear models (HLM) controlling for demographics, followed by meta-analysis to assess effect heterogeneity and overall patterns for indicators like teacher-student relationships and disciplinary climate. Results show school-based social capital significantly predicts reading achievement beyond demographics, but its net explanatory power (1%–7.8% variance) and the effects of specific predictors vary significantly across countries (heterogeneity p  < .01). While some indicators show generally positive effects, others like parental involvement yield unexpected results in many contexts. Findings underscore the culturally contingent nature of social capital effects, highlighting limitations of universalist frameworks and standardized data, and calling for culturally sensitive policies and research.